Risk Factors for Uterine Disease in Dairy Cows - Klibs N.A. Galvão (EDIS)
Uterine diseases are highly prevalent in high-producing dairy cows. Predictors of uterine disease include traditional risk factors, BHBA blood concentration, NEFA blood concentration, neutrophil glycogen stores, and calcium. This 4-page fact sheet was written by Klibs N.A. Galvão and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, May 2012.